Achieving enhanced peroxidase-like activity in multimetallic nanorattles. Issue 39 (21st September 2022) - da Silva, Flavia G.; Formo, Eric V.; Camargo, Pedro H. C.
Abstract : Controlling the nanoparticle morphology enables multimetallic nanorattles to achieve an increase of 152-fold in the peroxidase-like activity relative to Au nanoparticles. Abstract : Gold nanoparticles (Au NPs) have been extensively used as artificial enzymes, but their performance is still limited. We address this challenge by focusing on multimetallic nanorattles comprising an Au core inside a bimetallic AgAu shell, separated by a void (Au@AgAu NRs). They were prepared by a galvanic replacement approach and contained an ultrathin and porous shell comprising an AgAu alloy. By investigating the peroxide-like activity using TMB oxidation as a model transformation, we have found an increase of 152 fold in activities for the NRs relative to conventional Au NPs. Based on the kinetics results, the NRs also showed the lowest K m, indicating better interaction with the substrate and faster product formation. We also observed a linear relationship between the concentration of the product and oxTMB as a function of H2 O2 concentration, which could be further applied for H2 O2 sensing applications (colorimetric detection). These data suggest that the NRs enable the combined effect of an increased surface area relative to solid counterparts, the possibility of exposing highly active surface sites, and the exploitation of nanoconfinement effects due to the void regions between the core and shell components. These results provide important insights into the optimization of peroxidase-like performances beyond what can be achieved in conventional NPs and may inspire the development of better-performing artificial enzymes.